PERFORMANCE EVALUATION OF REAL TIME PRECISE POINT POSITIONING FOR MULTI-GNSS CONCEPT - Karlitepe, Furkan; Tunalioglu, Nursu; Erdogan, Bahattin (YILDIZ TECHNICAL UNIV, 2020)
Today, Precise Point Positioning (PPP) technique is at the forefront of the Global Navigation Satellite Systems (GNSS) based point positioning in many applications. In particular, GNSS-based real-time PPP (RT-PPP) applications are significant for next-generation autonomous systems and geospatial industries. However, real-time corrections are required for these applications. Since 2003, International GNSS Service (IGS) has been preparing substructure for multi-GNSS applications within the context of multi-GNSS Experiment (MGEX) Project. In this study, two IGS MGEX stations were selected. These are equipped with GPS, GLONASS, Galileo and BeiDou systems' receivers, and provide real-time solutions. Then, eight scenarios were generated depending on the different satellite combinations. These scenarios were examined in terms of convergence time and positioning accuracy, and the performance of different satellite systems in RT-PPP analyses was revealed. BNC v2.12.6 software was used for all analyses. Regarding the results, it can be concluded that using the different satellite combinations results in shortening the convergence time in RT-PPP and increasing the positioning accuracy.
Keywords: Multi-GNSS; Real-Time PPP (RT-PPP); IGS MGEX; combined positioning; convergence time; EFFICIENT; PPP; Engineering